Análise dos conhecimentos pedagógicos de conteúdo expressos por licenciandos em matemática participantes do PIBID - Greco, Danilo de Souza (2022)
This work presents an analysis of the pedagogical content knowledge expressed by Mathematics undergraduates, participants of the Teaching Initiation Program – PIBID. This is a documentary research, in which the data were obtained through a document produced by the undergraduates, called portfolio, containing different narratives of the formative processes experienced in the PIBID. These data were analyzed based on the theoretical framework and contributions of Shulman (1986, 1987 and 2015), regarding the Knowledge Base for Teaching (BCE) and Pedagogical Content Knowledge (PCK). To carry out the research, a qualitative, descriptive approach was adopted, with methodological procedures of analysis supported by the analysis of Shuman (1986). The organization of the data relied on the help of tables, through which excerpts that showed some element of knowledge of the BCE were listed, based on episodes taken from the students' portfolios. The results of this research indicate that the knowledge of the undergraduates that stood out was the pedagogical content knowledge. These results point to the need for training programs for teaching with the knowledge necessary for educational practices in the classroom, considering as an example the PIBID and the importance of other researches that advance in the context of teaching science and mathematics.